Пошаговое объяснение:
5(x+2)=x-2*(5-x) 3*(1-x)-(2-x)=2 14-(4+2x)=1+x 3-x=1-7*(x+1)
5x+10=1 3-3x-2+x=2 14-4-2x=1+x 3-x=1-7x-7
5x=1-10 1-2x=2 10-2x=1+x 3-x=-6-7x
5x=-9 -2x=2-1 -2x-x=1-10 -x+7x=-6-3
x=9/5 -2x=1 -2x=-9 6x=-9
x=1/2 x=3 x=-3/
x - 28 = 40
x = 40 - 28
x = 12
ответ: 12
40 - х = 28
х = 40 - 28
х = 12
ответ: 12
5 * х = 125 : 5
5 * х = 25
х = 25 : 5
х = 5
ответ: 5
266 : х = 100 - 93
266 : х = 7
х = 266 : 7
х = 36
ответ: 36
4 * х = 28 * 10
4 * х = 280
х = 280 : 4
х = 70
ответ: 70
х : 4 = 10 + 28
х : 4 = 38
х = 38 : 4
х = ?
ответ: ?
Проверь последнее уравнение. Там кажется не та цифра.